Analysis of Key Aroma Active Compounds of Novel Qingke Baijiu by GC-MS/GC-O-MS Combined with PLSR - Yahui ZHAO; Pengfei LIAO; Lu CHEN; Yuhong ZHANG; Xuliang WANG; Yulong JIN; Jiajun YU; Hehe LI; Jinyuan SUN (Shipin gongye ke-ji)
A novel Qingke Baijiu was produced by the process of light-aroma Baijiu combined with high-temperature stacking process and using highland barley of Tibet as material. Three kinds of Qingke Baijiu samples were evaluated by quantitative descriptive analysis, and analyzed by liquid-liquid extraction combined with gas chromatography-mass spectrometry and gas chromatography-olfactometry-mass spectrometry and analyzed by partial least squares regression analysis to clarify the aroma characteristic of the novel Qingke Baijiu and to investigate the influence of different manufacturing process. A total of 139 volatile compounds and 57 aroma compounds were detected in three samples, which included 11 aroma active compounds with odor active value (OAV) greater than 1. The total concentration of volatile compounds was 1.4 times higher after secondary fermentation. The sorghum and Zao aromas increased in the samples after secondary fermentation, where ethyl caprylate, ethyl caproate, ethyl isovalerate, and guaiacol were the corresponding key differential compounds. The sorghum and Zao aromas decreased after high-temperature stacking process, while floral aroma increased. Compared with the samples without high-temperature stacking process, the OAV of isoamyl acetate, guaiacol and 4-methylguaiacol increased, while the OAV of ethyl butyrate, ethyl caproate, and ethyl caprylate declined. After high-temperature stacking process, the concentration of isoamyl acetate increased, which lead to stronger floral aroma, and the concentration of butyric acid, ethyl caproate, ethyl caprylate, and ethyl decanoate declined, which lead to weaker sorghum aroma.